ANALISIS PENDAPATAN USAHA TANAMAN HIAS â€œGETSEMANIâ€ DI KELURAHAN TAAS KECAMATAN TIKALA, KOTA MANADO (Income Analysis of â€œGetsemaniâ€ Ornamental Plant Business in Taas, Tikala District, Manado City) - Edis Wenda; Gene H. M. Kapantow; Martha M. Sendow (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to analyze the income of ornamental plant farming "Getsemani" in Taas of Tikala District, Manado City. This research was conducted from July to September 2020. The data used in this study were primary data. Primary data were obtained through direct interviews with the owner of the ornamental plant "Getsemani" using a list of questions.The results showed that the income of the Getsemani Ornamental Plants Business which consists of ornamental chives (Allium tuberosum), pilodenrol (Philodenron monstera deliciosa) and deer (Tabernaemontana corimbosa) in Taas Village, Tikala District, Manado City in one month was IDR 3,784,456. The business efficiency obtained by means of the R/C analysis was 1.56.